Construction of Ustadz Firanda Andirja Abidin's Da'wah on Youtube Account about Tahlilan - Saniatul Hidayah (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2024)
This paper will discuss the construction of tahlilan through da'wah from the Youtube account "Firanda Andirja", where the account has a routine in posting religious narratives containing the Qur'an and hadith. The delivery of da'wah on the account seems to have a significant influence in changing the audience's views on the practice of tahlilan, based on the Prophetic traditions and the views of the Shafi'iyyah Ulama. This paper is included in a literature study by referring to the theory presented by Stuart Hall, namely cultural studies. This theory helps in understanding how Islamic identity is presented and constructed in the media, as well as its impact on individual perception and identity. In the construction process, the author classifies three points that depart from Firanda Andirja's da'wah in the content regarding tahlilan, namely; the hadith that explains tahlilan as a religious tradition, the hadith that shows the arrival of the reward to the deceased, and the hadith that explains about serving dishes to the family of the deceased. From the da'wah delivered, it triggers a variety of responses among audiences (netizens) who comment on the column provided. The results found, that Ustadz Firanda Andirja's da'wah in his Youtube account with the content title 'Tahlilan Bid'ah?' has a bias in understanding and narrating his studies, this is evidenced by his understanding which tends to be textualist and subjective. This then has positive and negative implications for social media users.